2017
DOI: 10.1002/hep.28989
|View full text |Cite
|
Sign up to set email alerts
|

The core domain of hepatitis C virus glycoprotein E2 generates potent cross‐neutralizing antibodies in guinea pigs

Abstract: A vaccine that prevents hepatitis C virus (HCV) infection is urgently needed to support an emerging global elimination program. However, vaccine development has been confounded because of HCV's high degree of antigenic variability and the preferential induction of type‐specific immune responses with limited potency against heterologous viral strains and genotypes. We showed previously that deletion of the three variable regions from the E2 receptor‐binding domain (Δ123) increases the ability of human broadly n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
96
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(104 citation statements)
references
References 43 publications
4
96
1
Order By: Relevance
“…The Δ123 protein may also limit the presentation of nonneutralizing domain A epitopes which are exposed at post-CD81 binding stages in virus entry and represents an antigenic cluster accounting for a substantial portion of isolate-specific antibody responses to E2 (13). We recently reported that higher-molecular-weight forms of Δ123 protein also generate more potent neutralizing antibodies in vivo due at least in part to the burial of nonneutralizing domain A epitopes at intermolecular interfaces (19). The Δ123 protein therefore represents a unique tool to further investigate how such immunogenic sites are presented within E2 and to evaluate the potential of recombinant E2 as a vaccine candidate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Δ123 protein may also limit the presentation of nonneutralizing domain A epitopes which are exposed at post-CD81 binding stages in virus entry and represents an antigenic cluster accounting for a substantial portion of isolate-specific antibody responses to E2 (13). We recently reported that higher-molecular-weight forms of Δ123 protein also generate more potent neutralizing antibodies in vivo due at least in part to the burial of nonneutralizing domain A epitopes at intermolecular interfaces (19). The Δ123 protein therefore represents a unique tool to further investigate how such immunogenic sites are presented within E2 and to evaluate the potential of recombinant E2 as a vaccine candidate.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant E2 and E1E2 have proven to be highly immunogenic; however, neutralizing antibody responses show limited breadth of neutralization (16)(17)(18)(19). E2 exhibits the highest degree of amino acid variability encoded in the HCV genome, which localizes to three discrete variable regions.…”
mentioning
confidence: 99%
“…Neutralisation against cell culture-derived HCV (HCVcc) was performed as previously described with GT2a Jc1Flag2 (p7-nsGluc2A) and GT3a (S52) JFH-1 chimeras. 24 HCV E1E2 binding and competition ELISAs were performed as described previously. 4 Briefly, microtiter plates were pre-coated with Galanthus nivalis lectin (GNA), blocked with 5% non-fat dry milk before capturing GT1 (H77.20) or GT3 (UKN3A13.6) E1E2 for 1.5 h at saturating concentration.…”
Section: Hcv Neutralisation and E1e2 Productionmentioning
confidence: 99%
“…The hypervariable region 1 (HVR1) within E2 forms an immunodominant epitope in HCV infection, however antibodies that target this region are highly strain specific. Furthermore, HVR1 is prone to high levels of mutation, driving immune escape, 13 making it unsuitable for vaccine design. Characterising the immunodominance hierarchy of epitopes with favourable neutralising potential is therefore required to understand what constitutes protective immunity to HCV.…”
Section: Introductionmentioning
confidence: 99%
“…There have been a number of successful structure-based vaccine designs for variable viruses such as influenza (12,13), HIV (14,15), and RSV (16,17) where rationally designed immunogens optimize presentation of key conserved epitopes, mask sites using N-glycans, or stabilize conformations or assembly of the envelope glycoproteins. Recent studies have reported use of several of these strategies in the context of HCV glycoproteins, including removal or modification of N-glycans to improve epitope accessibility (18,19), removal of hypervariable regions (18,20,21), or presentation of key conserved epitopes on scaffolds (22,23). However, such studies have been relatively limited compared with other viruses, in terms of design strategies employed and number of designs tested, and immunogenicity studies have not shown convincing improvement of glycoprotein designs over native glycoproteins in terms of neutralization potency or breadth (18,21), with the possible exception of an HVR-deleted high molecular weight form of the E2 glycoprotein that was tested in guinea pigs (20).…”
Section: Introductionmentioning
confidence: 99%